Analysis of the Influence of Order Variation Factors on the Costs and Time of Implementing Channel Diversion Infrastructure Construction Projects in Residential Areas - Hindami, Ghazi Ghossan; Suroso, Agus; Amin, Mawardi (Universitas Ibn Khaldun Bogor, 2024)
Tangerang is one of the big cities that is developing in Indonesia. Along with the development of the city, one sector that is increasingly developing is the housing sector. In implementing construction projects, problems are often faced, one of which is the occurrence of changes. Almost all existing projects experience variation orders (VO). Variation orders always have cost and time implications. Whatever the variation, there will be risks to the work being done, both in terms of work delays and additional costs that must be borne. Research using the SEM PLS method was carried out to find out what factors cause variation orders and how they affect time and cost performance in channel diversion infrastructure projects in residential areas. Based on the results of responses from correspondents, the significant value that influences project performance is planning and design with indicators of errors in planning drawings. Based on the results of the cost performance analysis for the amount of costs resulting from variation orders on work, the total increase was IDR. 10.516.305.346 and for less work the total is IDR. 6.628.461.533 around 12.96% of the initial contract price and the results of the time performance analysis for the amount of time resulting from variation orders on the project work show that there was a time extension of 5 months or 125%.